2020
DOI: 10.1186/s12909-020-02299-8
|View full text |Cite
|
Sign up to set email alerts
|

Fostering teaching-learning through workplace based assessment in postgraduate chemical pathology residency program using virtual learning environment

Abstract: Background The principle of workplace based assessment (WBA) is to assess trainees at work with feedback integrated into the program simultaneously. A student driven WBA model was introduced and perception evaluation of this teaching method was done subsequently by taking feedback from the faculty as well as the postgraduate trainees (PGs) of a residency program. Methods Descriptive multimethod study was conducted. A WBA program was designed for PGs in Chemical Pathology on Moodle and forms utilized were cas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Online delivery of educational content brings forth a multitude of advantages, predominantly cost-effectiveness, scalability, replicability and increased accessibility (32)(33)(34)(35). Multiple reports, including those from Pakistan, have demonstrated strong support for online learning (36)(37)(38), while others have suggested that traditional modalities of learning may be more effective in enhancing knowledge outcomes (39,40). While it does not compare the two, our study does resonate with the support expressed for online teaching-learning mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Online delivery of educational content brings forth a multitude of advantages, predominantly cost-effectiveness, scalability, replicability and increased accessibility (32)(33)(34)(35). Multiple reports, including those from Pakistan, have demonstrated strong support for online learning (36)(37)(38), while others have suggested that traditional modalities of learning may be more effective in enhancing knowledge outcomes (39,40). While it does not compare the two, our study does resonate with the support expressed for online teaching-learning mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Appreciating these concerns against the backdrop of the cost of implementing WBA in well-resourced contexts [ 34 , 35 ] provides further opportunity for reflection, especially around long-term sustainability of WBA in a LMIC. However, there is evidence from other resource-constrained environments such as Pakistan [ 40 ] that WBA can be adapted to resource-scarce contexts if the design and implementation process is sensitive to these contextual realities. This discussion emphasises the need for effective alignment and collaboration between decision-making structures, those with access to resources, and those tasked with implementing WBA in clinical spaces.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Jafri L et al (2020) found that it is prudent to promote the implementation of virtual learning environments (VLEs) in the context of the WBA program. Real-time data collection for formative assessments is now feasible because of the development of VLE and related software systems [40]. Denison A. et al (2016) found that, when compared to the conventional, paper-based data-gathering method, the usage of tablet devices in OSCE exams is linked to better examiner comments for use as feedback [41].…”
Section: E-learning Platforms For Formative Assessmentsmentioning
confidence: 99%